Natural balancing of three-phase 2-cell and 3-cell multicell converters - Salagae, Isaac Mahijoko (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Electrical and Electronic Engineering))--University of Stellenbosch, 2010.